The Politeness in The Poetry of Abu Al-Hasan Al-Husari Al-Qayrawani (Pragmatic Study) - Sekou Kouyate (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2022)
The research aims to clarify the concept of politeness and its forms, and to shed light on the relationship of the phenomenon of politeness with other similar phenomena, such as politeness and differentiation between them, and to highlight the rules of the principle of politeness and the rules branching on this principle, and to explore the phenomenon of politeness in the poetry of Abu al-Hasan al-Husari al-Qayrawani, the blind, by monitoring models a function of it. The researcher used the inductive analytical method, that is, the method of careful reading of Al-Hosary's poems, and extracting and analyzing the evidence in which the phenomenon of politeness is evident. One of the most prominent results of the research was that the features of positive politeness emerged in the poet in many rules, including: tact, generosity, skepticism, approval, humility, courtship, and agreement, and each rule was enriched with meanings worthy of it from the researcher's point of view, as the features of negative politeness also emerged in different models as well, including: direct request, objection to others, sarcasm, objection and sarcasm together, self-defense, directing the recipient to observe the sanctity of self, the sanctity of belief, and threat .